The Perspective of Hydropower as Renewable Energy - Behrouzi, Fatemeh; Abdul Malik, Adi Maimun; Ahmed, Yasser Mohamed; Nakisa, Mehdi (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2014)
According to environmental impact of fossil fuel, growth population and demand for energy, it is compulsory to replace the fossil fuel with renewable energy. Hydropower as a renewable energy possesses a lot of potential to provide energy and it is essential to improve the kinetic energy devices to harness the energy of water.